A Review of Wind Tunnel Based Virtual Flight Testing Techniques for Evaluation of Flight Control Systems - Min Huang; Zhong-wei Wang (International Journal of Aerospace Engineering)
Wind tunnel based Virtual Flight Testing (VFT) is a dynamic wind tunnel test for evaluating flight control systems (FCS) proposed in recent decades. It integrates aerodynamics, flight dynamics, and FCS as a whole and is a more realistic and reliable method for FCS evaluation than traditional ground evaluation methods, such as Hardware-in-the-Loop Simulation (HILS). With FCS evaluated by VFT before flight test, the risk of flight test will be further reduced. In this paper, the background, progress, and prospects of VFT are systematically summarized. Specifically, the differences among VFT, traditional dynamic wind tunnel methods, and traditional FCS evaluation methods are introduced in order to address the advantages of evaluating FCS with VFT. Secondly, the progress of VFT is reviewed in detail. Then, the test system and key technologies of VFT for FCS evaluation are analyzed. Lastly, the prospects of VFT for evaluating FCS are described.